Designing interconnected haptic interfaces and actuators for teleoperations in mobile ad hoc networks. (28th February 2020) - Kokkonis, George; Gounopoulos, Elias; Tsiamitros, Dimitrios; Stimoniaris, Dimitrios; Fragulis, George F.
The growing acceptance of wireless ad hoc networks in war situations, emergency situations, research applications, and conference rooms has resulted in the massive growth of these networks. Interconnecting haptic interfaces in virtual environments is rather a demanding task. This paper presents the topology of the mobile ad hoc networks. Moreover, it outlines the thresholds, the limitations, and the techniques for using haptic interfaces for teleoperations in a mobile ad hoc network. Routing algorithms and congestion control techniques for using haptic interfaces in mobile ad hoc networks are analysed. Simulations are taken place in order to test whether an ad hoc network can support the interconnection of haptic interfaces. Resulting this, we could say that on-demand protocols, such as DSDV, are suitable for networks with a large number of nodes and frequent modifications of network topology.